2014
DOI: 10.4238/2014.may.16.14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of overweight and obesity among individuals over 40 years old in Luzhou city

et al.

Abstract: ABSTRACT. In this study, a survey was conducted through questionnaire distribution and physical examinations were performed in 10,150 residents that were over 40 years old in Luzhou city. Respondents were selected by the multi-stage sampling method. The mean body mass index (BMI) of the sample population was 23.9 ± 3.3 kg/m 2 . Among men, BMI showed a negative relationship with increasing age (P < 0.05), whereas among women, it showed a positive relationship (P < 0.001). The rates of overweight and obesity inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous studies in adults in China found that age, educational level, a sedentary lifestyle and family history of diabetes were associated with increased prevalence of diabetes and prediabetes symptoms (Zeng et al., ). In addition, it has been recommended that people of 40–69 years of age should be the focus of interventions to prevent diabetes (Chen, Zhou, Cai, Huang, & Xu, ), which is in accordance with the present study's population.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in adults in China found that age, educational level, a sedentary lifestyle and family history of diabetes were associated with increased prevalence of diabetes and prediabetes symptoms (Zeng et al., ). In addition, it has been recommended that people of 40–69 years of age should be the focus of interventions to prevent diabetes (Chen, Zhou, Cai, Huang, & Xu, ), which is in accordance with the present study's population.…”
Section: Discussionmentioning
confidence: 97%